Geographic Labour Mobility - Productivity Commission (Canberra, ACT, 2014)
Geographic labour mobility is helping the economy adjust to major structural change, according to a research report released by the Productivity Commission. Generally people are moving to areas with better employment and income prospects, and employers are using a range of sources to attract employees with the required skills. In addition to permanent relocation, alternate forms of mobility are offering considerable flexibility in the labour market. The increased use of fly-in, fly-out (FIFO) practices and temporary immigration have been critical to meeting peaks in labour demand in many parts of the country. The study contributes to understanding of why people move. Commissioner Alison McClelland said: "For individuals, life events and family circumstances appear to be the most important factors in decisions whether to relocate for work. Factors related to housing, employment, local infrastructure and a person's level of education also play a prominent role." At an aggregate level, a region's size, distance from other regions, and economic opportunities are the main determinants of geographic labour mobility. While the study found some problems, particularly the persistence of high unemployment in some regions, there are no simple levers that governments can use to influence where people live and work. The Commission's recommendations are mostly aimed at broader structural reform, which will also assist employment mobility: alteration of the tax mix as it affects housing; improving the efficiency of land-use planning and land release; reviewing rent assistance and the supply of affordable rental properties available to people on low incomes; improving programs that assist unemployed people to find employment in other locations; and, restoring failing efforts to reduce occupational licencing barriers to mobility. There are gaps in the understanding and measurement of geographic mobility, particularly of temporary or 'service populations'. The Commission finds that more can be done in this area, in particular improving access to administrative data so that Agency holdings are available for analysis.
Research Report
Keywords: Employment; Employment -- Unemployment; Income & Finance; Employment -- Labour mobility; Income, wealth and finances; Labour market; Employment; Income & Finance; Labour mobility; Unemployment; Income, wealth and finances; Employment and unemployment